The Importance Of English Vowel In English Linguistics For Literacy Study - Masita Hamidiyah; Azzahra Natasya; Yani Lubis (Lembaga Pengembangan Kinerja Dosen, 2023)
English is a native-speaking language hundreds of millions of the world's population consisting of Americans, Australia, New Zealand, Canada and of course·only the British themselves. This fact allows the emergence of several English variants or varieties; Among another emergence of British English and American English. In the world of education, English as a language foreigners in Indonesia, the second variant has not received attention. Most English teaching institutions without be the choice of certain English variants. On Basically, the official provisions regarding this matter are not yet there is. However, there are variants of British English and American English can bring teacher doubts in dealing with abnormalities, vowel, vocabulary, or pronunciation the language. This is one of the considerations for the need to know English variants for prospective teachers and students English teacher, especially when the American influence is growing.